Discovery of a new class of orthosteric antagonists with nanomolar potency at extrasynaptic GABA(A) receptors - Falk-Petersen, Christina Birkedahl (Sci Rep, 2020)
Brain GABA(Α) receptors are ionotropic receptors belonging to the class of Cys-loop receptors and are important drug targets for the treatment of anxiety and sleep disorders. By screening a compound library (2,112 compounds) at recombinant human α(4)β(1)δ GABA(Α) receptors heterologously expressed in a HEK cell line, we identified a scaffold of spirocyclic compounds with nanomolar antagonist activity at GABA(Α) receptors. The initial screening hit 2027 (IC(50) of 1.03 μM) was used for analogue search resulting in 018 (IC(50) of 0.088 μM). 018 was most potent at α(3,4,5)-subunit containing receptors, thus showing preference for forebrain-expressed extrasynaptic receptors. Schild analysis of 018 at recombinant human α(4)β(1)δ receptors and displacement of [(3)H]muscimol binding in rat cortical homogenate independently confirmed a competitive profile. The antagonist profile of 018 was further validated by whole-cell patch-clamp electrophysiology, where kinetic studies revealed a slow dissociation rate and a shallow hill slope was observed. Membrane permeability studies showed that 2027 and 018 do not cross membranes, thus making the compounds less attractive for studying central GABA(Α) receptors effects, but conversely more attractive as tool compounds in relation to emerging peripheral GABA(Α) receptor-mediated effects of GABA e.g. in the immune system.